Inequality in life spans and a new perspective on mortality convergence across industrialized countries - Edwards, Richard; Tuljapurkar, S.
gráfs.
pp. 645-674
Keywords: Paises Desarrollados; Desigualdad y Calidad de Vida; Mortalidad; Esperanza de Vida